Medical management of 26 clinical cases of horses with esophageal obstruction treated during a six-year period (2008-2014): review, diagnosis, and protocols used - Estrada-McDermott, Juan M. (2025)
This article addresses esophageal obstruction in horses to raise awareness about the problem, make a specialized literature review on the topic, recommend an early differential diagnosis, and propose therapeutic alternatives for effective management of the situation. Diagnosis relies primarily on a comprehensive medical history and a systematic general clinical examination, supported, in some cases, by laboratory and imaging studies, including radiography, ultrasound scanning, and endoscopy. Medical management should focus on providing adequate metabolic support therapy, correcting the obstruction to prevent permanent esophageal damage, and utilizing systemic antibiotics to address secondary bacterial pneumonia resulting from bronchoaspiration. The article outlines a clinically successful protocol, endorsed by literature and based on over 30 years of the authors’ professional experience.